Simulations of the Crude Oil Tank Refurbishment Project Risks Using Monte Carlo - Ari Sandhyavitri; Arvin Arvin; Fajar Restuhadi (Journal of Applied Materials and Technology, 2021)
Simulation technology has assisted project stakeholders in predicting a range of the project results in the future under risks and uncertainties. The objectives of this article are to improve a comprehensive project planning in the perspective of the project scheduling by conducting simulations for the refurbishment of crude oil tank project risks using Monte Carlo simulations. The practical approaches for simulating the risks encompassed 3 stages: risk identification, assessment, and risk analysis using the Monte Carlo simulations. The implementation of Monte Carlo simulation in the form of stochastic approach however were not new, but the application of these approaches in the area of oil industrial projects was challenging. A Free Water Knock-Out (FWKO) tank project located in Duri, Indonesia was taken as a case study. The initial FWKO project duration was set up to be 180 working days, and it was delayed (up to 140% from the initial duration of the project planning). This study conducted deep questioner surveys from 25 oil industry stakeholders. It was identified 29 risk factors have been considered as the major causes of the project delay. The risk factors were then calculated qualitatively for performing risk indexes. Based on the risk simulations (after 1000 iterations) using Monte Carlo simulations utilizing @risk application package (under uncertainties) there was found that the possibility of this project would experience delays at the range of 47 days (126%) to 80 days (144%) from the initial project planning. This simulation had also identified the most sensitive activities causing project delays. The results was presented in the form of the spider graph diagram which assisted the project main stakeholders in developing a strategic decision during project planning phase.